Combined remediation mechanism of bentonite and submerged plants on lake sediments by DGT technique. (July 2022) - Liu, Yunli; Bai, Guoliang; Zou, Yilingyun; Ding, Zimao; Tang, Yadong; Wang, Rou; Liu, Zisen; Zhou, Qiaohong; Wu, Zhenbin; Zhang, Yi
Abstract: The diffusive gradients in thin films (DGT) technique was applied to determine the mechanism by which bentonite improves the eutrophic lake sediment microenvironment and enhances submerged plant growth. The migration dynamics of N, P, S, and other nutrient elements were established for each sediment layer and the remediation effects of bentonite and submerged plants on sediments were evaluated. Submerged plant growth in the bentonite group was superior to that of the Control. At harvest time, the growth of Vallisneria spiralis and Hydrilla verticillata was optimal on a substrate consisting of five parts eutrophic lake sediment to one part modified bentonite (MB5/1). Bentonite addition to the sediment was conducive to rhizosphere microorganism proliferation. Microbial abundance was highest under the MB5/1 treatment whilst microbial diversity was highest under the RB1/1 (equal parts raw bentonite and eutrophic lake sediment) treatment. Bentonite addition to the sediment may facilitate the transformation of nutrients to bioavailable states. The TP content of the bentonite treatment was 22.47%–46.70% lower than that of the Control. Nevertheless, the bentonite treatment had higher bioavailable phosphorus (BIP) content than the control. The results of this study provide theoretical and empirical references for the use of a combination of modified bentonite and submerged plants to remediate eutrophic lake sediment microenvironments. Graphical abstract: Image 1 Highlights: DGT technique was applied to reveal the combined remediation mechanism. Remediation effects of bentonite and submerged plants on sediments were evaluated. Bentonite and submerged plants improved eutrophic lake sediment microenvironment. Bentonite was conducive to rhizosphere microorganism proliferation. Bentonite enhanced submerged plant nutrient bioavailability in lake sediment.